2012
DOI: 10.1186/ar3831
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an immunotoxin to folate receptor beta in the intra-articular treatment of antigen-induced arthritis

Abstract: IntroductionWe previously demonstrated that synovial sublining macrophages express folate receptor beta (FRβ). The aim of this study was to evaluate the efficacy of intra-articular administration of a recombinant immunotoxin to FRβ for treating rat antigen-induced arthritis.MethodsA monoclonal antibody (mAb) to rat FRβ was produced by immunizing mice with B300-19 cells (murine pre-B cells) transfected with the rat FRβ gene. Recombinant immunotoxin was prepared by conjugating the Fv portion of the anti-rat FRβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…MTX exhibits a relatively low binding affinity for FR, hence more selective targeting of folate antagonists to FR expressing cells in the synovium may be of value if therapy with MTX fails [12]. Other therapy strategies could include folate-immunoconjugates [41] and folate-conjugated vincristine [42]. …”
Section: Discussionmentioning
confidence: 99%
“…MTX exhibits a relatively low binding affinity for FR, hence more selective targeting of folate antagonists to FR expressing cells in the synovium may be of value if therapy with MTX fails [12]. Other therapy strategies could include folate-immunoconjugates [41] and folate-conjugated vincristine [42]. …”
Section: Discussionmentioning
confidence: 99%
“…FRβ-positive macrophages were identified in the synovial lining and sublining of RA and OA patients. In a rat arthritis model, FRβ-positive macrophages could be targeted with FRβ antibody-conjugated immunotoxins, leading to reduced joint swelling [96]. Beyond this, these immunotoxins also had a tumor-suppressive effect in a rat C6 glioma tumor xenograft model [97].…”
Section: Antifolates In Immune Diseasesmentioning
confidence: 97%
“…There is a good deal of recent literature on macrophages in RA, and the potential to induce macrophage apoptosis, to deplete synovial macrophages, or to change the macrophage polarisation from a M1 (classical, infl ammatory) to M2 (alternative, anti-infl ammatory) [ 39 -41 ]. It has been demonstrated that RA synovial lining macrophages express folate receptor-β, and there has been an interest in targeting this to administer either folate antagonists [ 42 ] or an immunotoxin reducing the number of macrophages and inducing benefi t in an animal model of arthritis [ 43 ].…”
Section: The Role Of Macrophages In Ramentioning
confidence: 99%